Fifteen years of sector-wide approach (SWAp) in Bangladesh health sector: an assessment of progress - Ahsan, Karar Zunaid (Health Policy Plan, 2016)
The Ministry of Health and Family Welfare (MOHFW) of the Government of Bangladesh embarked on a sector-wide approach (SWAp) modality for the health, nutrition and population (HNP) sector in 1998. This programmatic shift initiated a different set of planning disciplines and practices along with institutional changes in the MOHFW. Over the years, the SWAp modality has evolved in Bangladesh as the MOHFW has learnt from its implementation and refined the program design. This article explores the progress made, both in terms of achievement of health outcomes and systems strengthening results, since the implementation of the SWAp for Bangladesh’s health sector. Secondary analyses of survey data from 1993 to 2011 as well as a literature review of published and grey literature on health SWAp in Bangladesh was conducted for this assessment. Results of the assessment indicate that the MOHFW made substantial progress in health outcomes and health systems strengthening. SWAps facilitated the alignment of funding and technical support around national priorities, and improved the government’s role in program design as well as in implementation and development partner coordination. Notable systemic improvements have taken place in the country systems with regards to monitoring and evaluation, procurement and service provision, which have improved functionality of health facilities to provide essential care. Implementation of the SWAp has, therefore, contributed to an accelerated improvement in key health outcomes in Bangladesh over the last 15 years. The health SWAp in Bangladesh offers an example of a successful adaptation of such an approach in a complex administrative structure. Based on the lessons learned from SWAp implementation in Bangladesh, the MOHFW needs to play a stronger stewardship and regulatory role to reap the full benefits of a SWAp in its subsequent programming.